Progress in Landslide Research and Technology, Volume 1 Issue 2, 2022 - Alcántara-Ayala, Irasema; Arbanas, Željko; Huntley, David; Konagai, Kazuo; Mikoš, Matjaž; Sassa, Kyoji; Sassa, Shinji; Tang, Huiming; Tiwari, Binod (Progress in Landslide Research and Technology, 2023)
This open access book provides an overview of the progress in landslide research and technology and is part of a book series of the International Consortium on Landslides (ICL). It gives an overview of recent progress in landslide research and technology for practical applications and the benefit for the society contributing to understanding and reducing landslide disaster risk.